Changes in facial expressions in patients with Parkinson's disease during the phonation test and their correlation with disease severity. (March 2022) - YANG, Liqiong; CHEN, Xiangling; GUO, Quanhao; ZHANG, Jing; LUO, Man; CHEN, Xiaqing; WEN, Yanxia; ZOU, Xianwei; XU, Fan
Highlights: This study found that the facial expressions of neutral feelings, happiness, surprise, valence and arousal were significantly lower in patients with PD, whereas those of sadness, anger, fear, and disgust were significantly higher, as compared to the respective ones in healthy subjects. Furthermore, our data indicated significant correlations between these deficits in facial expressions and the severity of PD. Collectively, these results strengthen our understanding of the significance of "mask face" changes in patients with PD, which may accelerate the discovery of novel biomarkers in this disease. We thus believe that our findings will be of interest to physicians, nurses, general caregivers, and the public. Abstract: Purpose: Parkinson's disease (PD) is a serious neurodegenerative disease affecting more than one million people globally. A mask-like face is an important early motor symptom of PD; it develops gradually and is asymptomatic. However, the relationship between the severity of PD and changes in facial expressions remains unclear. We aimed to elucidate the inner linkage. Method: From January to September 2019, we recruited 16 PD patients in the First Affiliated Hospital of Chengdu Medical College and 16 healthy individuals. Participants performed phonation tests, during which their facial expressions were recorded, and the changes were analyzed using Noldus FaceReader 7.0. Results: Facial expressions of neutral feelings, happiness, surprise, valence, and arousal during single-, double- and multiple-syllable phonation tests were significantly lower in patients with PD, whereas those of sadness, anger, scared, and disgust were significantly higher compared to those in healthy subjects. There were significant correlations between the changes in facial expressions and the severity of PD. Conclusion: Patients with PD displayed a decrease in positive facial expressions, whereas they presented an increase in negative expressions. This is helpful for further research on facial dyskinesia in PD.